АНАЛИЗ ИЗУЧЕНИЯ ФЕНОМЕНА ПРОЦЕССА СЕГРЕГАЦИИ - Васильев А.М. (My University, 2006)
В статье дан обзор исследований по процессу сегрегации. Приведены конкретные примеры аппаратов, на которых проявляется расслоение. Выявлена, прослежена и обоснована роль стратификации на процессы разделения в гравитационных методах обогащения.

In given article the review of researches on process segregation is resulted. Concrete examples of devices on which stratification is shown are resulted. The role of stratification on processes of division in gravitational methods of enrichment is revealed, tracked and proved.
Keywords: 658.52